Clinicopathological features of combined hepatocellular-cholangiocarcinoma with sarcomatous change: Case report and literature review. Issue 3 (January 2018) - Gu, Qianru; Yu, Xia; Chen, Hanbin; Chen, Guorong
Abstract: Rationale: Combined hepatocellular-cholangiocarcinoma (cHCC-CC) is a rare subtype of primary liver malignancy comprising <1.5% of all primary liver tumors. Sarcomatoid changes in cHCC-CC are even rarer. Due to the rarity of this subtype, its clinicopathological feature is poorly understood. Therefore, here we report 2 tumors. Patient concerns: The first patient was a 44-year-old man with 5-year history of hepatitis B-induced cirrhosis. The resection of right liver revealed a 2.5 × 2.5 × 2 cm tumor mass. Histologically, the tumor showed areas of the typical moderately differentiated HCC. An intermingled adenocarcinoma with pleomorphic and spindle-shaped cells was also identified. The second case involved a 54-year-old man with a history of hepatitis B-induced cirrhosis. A 3.5 × 3 × 3 cm mass was found in the middle left of falciform ligament. Microscopically, the tumor consisted of spindle-shaped sarcomatoid carcinoma cells mixed with typical well-differentiated HCC and well-differentiated CC. Diagnoses: According to the clinicopathological features, diagnosis of cHCC-CC with sarcomatous change was made. Interventions: In the first case, right lobectomy of the liver was performed. The second patient underwent laparoscopic, hepatic left lateral lobectomy. Outcomes: The first patient was alive and well 10 years after the surgical resection without additional treatment. In second case, at 8 months after surgical resection, there was no evidence of recurrence or metastasis. Lessons: In this report, we describe 2 rare cases of cHCC-CC with sarcomatous change, and findings are helpful for the pathologists would like to further identify the clinicopathological features of this rare tumor.